Growth parameter, mortality, recruitment pattern, and exploitation rate of white shrimp Penaeus indicus in northern coastal waters of Western Central Java, Indonesia - SURADI WIJAYA SAPUTRA; ANHAR SOLICHIN; WIWIET TEGUH TAUFANI; SITI RUDIYANTI; NINIEK WIDYORINI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Saputra SW, Solichin A, Taufani WT, Rudiyanti S, Widyorini N. 2019. Growth parameter, mortality, recruitment pattern, and exploitation rate of white shrimp Penaeus indicus on the northern coast of Central Java, Indonesia. Biodiversitas 20: 1318-1324. The aims of this study were to know the growth parameters, first lenght captured (Lc), mortality, recruitment pattern, and the exploitation rate of white shrimp (Penaeus indicus H.Milne Edwards, 1837) in the Western Coastal North Central Java Sea, Indonesia. Samples were collected from May 2016 to July 2017 using survey method and direct observations on fishing unit areas. The results showed that the relationship of the carapace length and weight is allometric. Based on the estimates of von Bertalanffy growth equation to the carapace length, the growth parameters of CL? and K values in male were 37 mm and 0.97, while in female were 38.5 mm and 0.85. While, the rates of total mortality (Z), natural mortality (M), and fishing mortality (F) were 3.5, 1.67, and 1.84 for males, and 5.03, 1.51, and 3.52 for females, respectively. The exploitation rate (E) of male shrimp was 0.52 and of female was 0.7 indicating that female shrimp get higher capture pressure than the males. It also showed that the rate of exploitation has to exceed the optimum sustainable yield (E>0.5). Time recruitment occurred throughout the year, with two peak seasons, i.e., in April-June and September-November. Moreover, the length of the carapace during recruitment was 15-20 mm. While the carapace length of the first caught (CL?50) was 18.3 mm for male and 17.6 mm for female indicating that the P. indicus caught was still in the small size, as well as below the first mature gonad (CLm50 = 22-39 mm). This is because the mesh size of cod-end is 0.75 inches or about 2 cm.